Body Indices and Population Dynamics of Setipinna breviceps (Cantor, 1849) from Batang Lassa Estuary, Sarawak, Malaysia: Population dynamics of Setipinna breviceps from Batang Lassa - M. GOLAM MUSTAFA; AMY HALIMAH RAJAEE; HADI HAMLI; KHAIRUL ADHA A. RAHIM (Borneo Journal of Resource Science and Technology, 2023)
The Setipinna breviceps is a commercially important and highly esteemed food fish. This species has scant of scientific formation particularly on population parameters like growth, mortality and recruitment. The present study aimed to estimate the body indices and population parameters of Setipinna breviceps of Batang Lassa Estuary (BLE). Samples were collected between April 2019 and September 2020. A local made bag net known as Gnian (mesh size 1.25 to 4.00 cm) was used for sampling the fish. A total of 287 qualified specimens were used for this study. The length and weight of individual fish was measured to the nearest 0.1 cm and 0.01 g, respectively. The length ranged from 5.50 to 24.00 cm and growth coefficient (b) was 2.563 (R2 = 0.87) which clearly indicated a negative allometric growth. About 50% of individuals showed flat or slender body (Kn<1) and 47% of the specimens were rounded shaped (Kn>1) while 2.44% of fishes measured an ideal shape (Kn = 1). The parameters of growth L∞, K and ϕ’ were estimated at 24.15 cm, 0.23 yr-2 and 2.13, respectively. The estimated natural mortality and fishing mortality were 0.74 and 0.29 yr-2, respectively and exploitation rate was 0.28. The recruitment pattern during the study was observed at two possible unequal peaks. The present study concluded that the anchovy was under exploited (E<0.5) as demonstrated by the under-sized fishes caught with small mesh size net. However, considering the minimum lengths and length at first catch, the BLE could be a productive nursery ground for S. breviceps. Therefore, management actions are required to avoid juvenile catches.